Dual biorecognition by combining molecularly-imprinted polymer and antibody in SERS detection. Application to carcinoembryonic antigen - Carneiro, Mariana (2019)
Supplementary data to this article can be found online at https://doi. org/10.1016/j.bios.2019.111761.